Символістські тенденції у творчості Олександра Олеся та європейських символістів - Цуркан, Ігор Миколайович; Tsurkan, Igor (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті окреслено вплив поетики символізму, найважливішим складником якої стала лірична настроє-вість і музичність поетичної фрази, які створювали в уяві візії, що презентували синтез життя природи й магічний вплив його на душу та настрій людини. Проаналізовано образ природи, що не ототожнюється зі світом реальним, а залишається тільки світом романтичним, набуваючи у своєму вираженні певних імпре-сіоністичних рис із кольористими крайобразами. Репрезентовано настрої людини, її почуття за допомогою символів, що відтворюють локальний колорит рідного краю у творчості Олександра Олеся та К. Тетмаєра.The creativity of Oleksandr Oles is marked by the influence of the romantic poetics, the most important component of which was the lyrical mood and the melodiousness of the phrases, that created the individual image of the spiritual being on the way to the beauty and dream. Oleksandr Oles brought the idea of the «inner individual», who revolted against the world and the public and government norms. The originality of the system of the artistic images, motives, spirits, rhythm and melodic absorbed the powerful lyricism of the poets' sensitive soul. That’s why the purpose of this article is the revelation the images, which creates the metaphorical universe, filled with symbols of the human existence. Obtaining the purpose envisages to investigate the system of symbols of Oleksandr Oles and European symbolists and to reveal its realization in the authors’ interpretations. The methods of the research is based on the main principles of the philological analysis of the text. The determined tasks foresee the use of elements of comparative and hermeneutic analysis as a general interpretation of literary texts.
The Symbolist Trends in the Works of Oleksandr Oles and European Symbolists
Keywords: символізм; образ; природа; символ; знак; мотив; душа; romanticism; image; nature; symbol; sign; motif; soul